Blockholder, Accounting Conservatism, Free Cash Flow, and The Cost Of Capital: What do We Know? - Santoso, Arif (Indonesian Journal of Economics, Social, and Humanities, 2025)
The usefulness of blockholders, accounting conservatism, and free cash flow on the cost of capital is a very important and controversial question. Companies in Indonesia still bear the highest cost of capital in ASEAN+3. This research aims to examine the influence of blockholders, accounting conservatism, and free cash flow on the cost of capital during the Covid-19 pandemic. A total of 68 food and beverage companies in 2020-2021 were used in this research. Data were analyzed using descriptive statistical analysis and panel data regression analysis using Eviews 12. The results showed that blockholders had a positive influence, accounting conservatism had a negative influence, and free cash flow had a positive influence on the cost of capital. The main conclusion from this research is that high accounting conservatism reduces the cost of capital and the size of the cost of capital in line with increasing the company's blockholders and free cash flow.